Influence of the Phaseolus vulgaris phaseolin level of incorporation, type and thermal treatment on gut characteristics in rats - Montoya Marmolejo, Carlos Aníbal; Lalles, JP; Beebe, Stephen E.; Montagne, L; Souffrant, WB; Leterme, P (Cambridge University Press, 2006)
Phaseolus vulgaris phaseolin has been shown to stimulate faecal losses of endogenous N in rats. Experiments with purified phaseolin were carried out in rats to test the hypothesis that these losses reflect intestinal disorders. Phaseolin composition varies depending on its constitutive subunits. Therefore, three phaseolin types (S, T, I) were tested. Phaseolin T was incorporated in varying levels (0, 33, 67 or 100% of the dietary protein) as raw material in experiment 1. In experiment 2, the three phaseolin types were incorporated at 50%, with or without previous thermic treatment. Raw casein was the basal protein source and was also heated in experiment 2. Faecal digestibility of phaseolin and gut integrity were evaluated in both experiments. The incorporation level or type of phaseolin had little effect on gross anatomy of gut segments but these factors influenced the weight and pH of fresh contents of the stomach and caecum (P<0·05). Raw phaseolin T incorporated at various levels led to an enlargement of duodenal villi together with a tendency for increased crypt depth in the jejunum (P=0·06). Activities of both alkaline phosphatase in the duodenum and aminopeptidase N in the ileum decreased (P<0·05) after thermal treatment of casein while they increased (P<0·05) for heat-treated phaseolin S and T, respectively. In conclusion, raw phaseolin had no effect on the tissue weight of gut segments and induced limited alterations in the small intestine. Differences due to phaseolin level or type were limited too.